The efficacy of Chinese herbal medicine on anxiety and depression in patients with chronic prostatitis complicated by sexual dysfunction: a systematic review and meta-analysis protocol - Xie, Zhaozhan; Zhang, Xuecheng; Li, Bai; Wang, Qi; Hou, Zhihui; Jia, Hongling; Zhang, Yongchen (Frontiers in Psychiatry, 2025)
BackgroundChronic Prostatitis (CP) is often accompanied by urinary symptoms such as dysuria and frequency, as well as sexual dysfunction including erectile dysfunction and reduced libido. Men with CP are at a significantly greater risk of developing anxiety and depression compared to healthy controls. Chinese Herbal Medicine (CHM) provides a holistic approach by simultaneously targeting inflammation, pelvic microcirculation, and neuropsychiatric pathways, which aligns with the multifactorial nature of CP. Therefore, this study will conduct a systematic review and meta-analysis to evaluate and summarize the efficacy of CHM for managing anxiety and depression in patients with CP complicated by sexual dysfunction.MethodsThis research will conduct a systematic search of four Chinese databases (China National Knowledge Infrastructure, Wanfang Database, China Biomedical Database, and VIP Database) as well as four international databases (PubMed, Web of Science, EMBASE, and Cochrane Library). It will focus on identifying randomized controlled trials (RCTs) that examine the effects of CHM interventions for CP complicated by sexual dysfunction and co-occurring anxiety and depression. The selected studies will then be subject to thorough screening and quality evaluation using standardized instruments.ResultsThe results of this study will provide a reliable basis for the efficacy of CHM for managing anxiety and depression in patients with CP complicated by sexual dysfunction.ConclusionsThis study will compare the clinical efficacy of CHM in managing anxiety and depression in patients with CP complicated by sexual dysfunction, thereby assisting clinicians and patients in selecting more effective intervention regimens during the clinical decision-making process.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD420251002787.